DESIGNING ADDIE MODEL-BASED SMART READING COMPREHENSION FOR ENGLISH READING CLASS - Ismail, Ishafiuddin; Amin, Fatimah Hidayahni; Patak, Andi Anto; Hanafie, Nurharsya Khaer; Luhriyani, Seny (Universitas Negeri Makassar, 2024)
This study is quantitative research that aims to know the development of ADDIE Model-based Smart Reading Comprehension Application for reading class at SMPIT Nurul Fikri Makassar and the validity, effectivity, and practicality criteria. The population was students of the ninth grade in SMPIT Nurul Fikri Makassar which consisted of four classes with a total population of 80 students. the researcher used a random sampling technique and the researcher chose one class from the four classes in Grade 9th. The sample in the class consists of 20 students. The development of a web-based smart reading application goes through a stage, namely prototype evaluation. At this evaluation stage, it is carried out to test whether the system being developed meets the valid, practical, and effective criteria. From two expert validators, an average of 3.68 was obtained with a percentage of 89.90%. As for the content aspect, an average of 4 is obtained with a percentage of 100%. As for the average results of the two expert validators above, if converted into a validity category table, a very valid category is obtained. Testing the practicality of the web-based smart reading application obtained a result of 82.83%. If converted into a table of percentage ranges and product criteria for practicality analysis, we get a practical category. The results of effectiveness obtained were 88.75 % with the highly effective criteria. Students’ perceptions of convenience, motivation, attractiveness, and usefulness toward the prototype of the reading comprehension application developed in this research showed a positive response.